Safety and feasibility of transulnar catheterization when ipsilateral radial access is not available. Issue 1 (5th August 2013) - Kedev, Sasko; Zafirovska, Biljana; Dharma, Surya; Petkoska, Danica
<x xml:space="preserve">Abstract</x> Objectives We evaluated the safety and feasibility of transulnar approach when ipsilateral radial access was not available. Methods and Results From March 2011 until February 2013, 476 consecutive patients who underwent transulnar catheterization were included in a single center prospective registry of effectiveness and safety. Diagnostic coronary angiography accounted for 42% of cases, percutaneous coronary intervention (PCI) for 38%, and 17% underwent carotid artery stenting. A subgroup analysis was done in 240 patients with documented ipsilateral radial artery occlusion (RAO). Procedural success was 97% with a crossover rate of 3% to transfemoral access. Hand ischemia was not observed in any patient on day 1 after procedure and on 1 month follow‐up. None of the patients showed ulnar nerve injury. Two patients developed major forearm hematoma that resolved without clinical consequences. Minor access site hematoma occurred in 8%. Severe clinical spasm occurred in two patients. Asymptomatic ulnar artery occlusion at 1 month follow‐up was detected in 3.1%. There was no difference between patients with or without RAO in terms of procedural success and any vascular complication. Conclusion Transulnar approach is safe and feasible alternative wrist access when performed by experienced radial operators, providing high success rate and low incidence of vascular complications. © 2013 Wiley Periodicals, Inc.